Beta-blocker use and COPD mortality: a systematic review and meta-analysis - Etminan, Mahyar (BioMed Central, 2012)
BACKGROUND: Despite the benefits of beta-blockers in patients with established or sub-clinical coronary artery disease, their use in patients with chronic obstructive pulmonary disease (COPD) has been controversial. Currently, no systematic review has examined the impact of beta-blockers on mortality in COPD. METHODS: We systematically searched electronic bibliographic databases including MEDLINE, EMBASE and Cochrane Library for clinical studies that examine the association between beta-blocker use and all cause mortality in patients with COPD. Risk ratios across studies were pooled using random effects models to estimate a pooled relative risk across studies. Publication bias was assessed using a funnel plot. RESULTS: Our search identified nine retrospective cohort studies that met the study inclusion criteria. The pooled relative risk of COPD related mortality secondary to beta-blocker use was 0.69 (95% CI: 0.62-0.78; I(2)=82%). CONCLUSION: The results of this review are consistent with a protective effect of beta-blockers with respect to all cause mortality. Due to the observational nature of the included studies, the possibility of confounding that may have affected these results cannot be excluded. The hypothesis that beta blocker therapy might be of benefit in COPD needs to be evaluated in randomised controlled trials.